Mineralocorticoid receptor antagonists in the treatment of central serous chorioretinopathy. (2nd January 2017) - Montorio, Daniela; Carnevali, Adriano; Sacconi, Riccardo; Capuano, Vittorio; Giuffrè, Chiara; Rabiolo, Alessandro; De Vitis, Luigi Antonio; Querques, Lea; Bandello, Francesco; Querques, Giuseppe
ABSTRACT: Introduction : Central serous chorioretinopathy (CSC) is one of the most common causes of central vision loss that primarily affects young adults. CSC is a multifactorial condition in which corticosteroids typically worsen the disease; this led to hypothesize the involvement of the mineralcorticoid receptor in its pathogenesis (due to the similar affinity of corticosteroids and aldosterone to this receptor). Area covered : Here, we perform a comprehensive literature review of all articles published in the English language, indexed on Pubmed, on the subject of 'Mineralocorticoid receptor antagonists in the treatment of CSC.' From these articles, the most salient disputes are presented. Expert commentary : Due to the lack of large randomized, controlled trials with long-term follow-up clearly demonstrating the positive effects of these treatments for CSC, no specific recommendation for the management of this disease has been defined yet. Despite lack of evidence level 1, mineralocorticoid receptor antagonists may represent an attractive therapeutic option for CSC. This review helps to clarity the efficacy and side effects of these drugs that maybe play an important role in treatment of CSC.